Islamic Family Law and the Recognition of Same-Sex Marriage: Controversial Issues in the Context of Human Rights - Achmad Fitrian (PT. Anagata Sembagi Education, 2024)
This study aims to examine the debate on Islamic family law regarding same-sex marriage in the context of human rights. In Islamic law, same-sex marriage is considered contrary to religious teachings, while human rights emphasize the principles of equality and non-discrimination. The conflict between religious norms and human rights demands is a major challenge, especially in countries with Islamic-based laws, including Indonesia. The research method used is a literature review by examining academic and legal sources. Data sources include the Qur'an, Hadith, fiqh books, and laws and regulations related to marriage in Indonesia. Secondary sources include academic books, scientific journals, and international legal documents related to human rights. Data were collected through literature studies from various academic databases and official legal sources. The results of the study show that Islamic family law still maintains the view that marriage is only valid between a man and a woman. Meanwhile, the human rights movement demands equality for the LGBT community. Countries with Islamic law, including Indonesia, still reject same-sex marriage despite global pressure. Therefore, a dialogue-based approach is needed to balance individual rights, religious values, and social harmony. Further studies are needed to formulate inclusive and fair solutions to this issue